(untitled) (Sotang, Yearly Peer Reviewed Journal, 2025)
Road traffic accidents are increasing at an alarming rate among adolescents whose driving is often linked with, curiosity, reckless behavior, speeding to show off, and using mobile phones while driving. The present study aimed to assess the knowledge regarding road traffic accidents among Students of Shree Jana Model Higher Secondary School, Birendranagar, 6 Surkhet. Drawing on a descriptive cross- sectional study, among118 adolescent students by adopting purposive sampling technique with census method. Semi structured self-administered questionnaire was developed which consisted of two parts. A questionnaire was distributed to the participants in their feasible time, 25 to 30-minute time was given to fill up the questionnaire and it was collected immediately after the completion. The data were analyzed through descriptive statistics (frequency, percentage) and inferential statistics (Chi-square).The result of the study showed that more than half of the respondents 67 (56.7%) had average knowledge, while 51 (43.3%) had good knowledge. There was no statistically significant association found between sociodemographic factors and the degree of knowledge, despite the different socio-demographic backgrounds and suggests students in various groups had comparatively similar understanding of traffic incidents. The study concludes that although a considerable proportion of students had a good knowledge of road safety, the majority still exhibited only an average level of knowledge, highlighting space for improvement. Therefore, the study recommends implementing diverse educational activities, such as road safety awareness programs and interactive sessions, to enhance awareness of traffic rules and safe driving practices which helps to reduce risky driving behaviors among adolescents.